The New international commentary on the Old Testament : Song of Songs - Longman, Tremper, III. (Grand Rapids, Mich. : William B. Eerdmans Publishing Company, 2001)
"Relationships are a wonderful, mysterious, often elusive, sometimes painful part of the human experience. The most intimate of all human relationships, according to the Bible, is that between a husband and a wife. It is not a surprise, therefore, that there is a book of the Bible, the Song of Songs, that focuses on this relationship. What is surprising is how little attention is given to the Song of Songs by scholars, by the church, and by readers of the Bible. With this volume, however, Tremper Longman III has written the finest commentary to date on the Song of Songs, unpacking for modern people what this ancient love poem says about the male-female relationship - and, by analogy, about God's love for his people."--Jacket.
I. Title 1 -- II. Authorship 2 -- III. Literary Style 9 -- IV. Language 17 -- V. Date 19 -- VI. Text 19 -- VII. History of Interpretation
Includes bibliographical references (pages 70-83) and indexes.
Keywords: Bible. -- Commentaries